Can we plan too much? the case of the 2010 metropolitan strategy for Adelaide - Bunker, Raymond (2015)
With a Labor government in power in South Australia since 2002, a series of interlocking plans for the state have been developed of which the most important are the strategic plan for the state, the strategic infrastructure plan for the state and the metropolitan strategy for Greater Adelaide. The metropolitan strategy of 2010 reflected the ambitious population and employment targets of the state strategic plan and provided a liberal supply of residential land for urban expansion together with ambitions for a more compact city with higher densities. There are inconsistencies in these objectives which have not been resolved and reflect the optimistic forecasts of the state strategic plan and the nature of the metropolitan planning process with strong input from the development industry. Preliminary evidence is that the plan is not tracking as proposed and more attention needs to be paid to short- and medium-term prospects, and community involvement particularly in strategic localities. Reproduced.
Keywords: Strategic planning